2019
DOI: 10.29157/etusbe.124
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Bi̇lgi̇ler Öğretmenleri̇ni̇n Teknopedagoji̇k Eği̇ti̇m Yeterli̇kleri̇ne İli̇şki̇n Görüşleri̇

Abstract: Bu çalışmada, sosyal bilgiler öğretmenlerinin teknopedagojik eğitim yeterliklerine ilişkin görüşleri belirlenmeye çalışılmıştır. Hem nicel hem nitel verilerin bir arada değerlendirildiği karma yöntemin kullanıldığı araştırmanın evrenini Afyonkarahisar merkeze bağlı ortaokullarda görev yapan 101 Sosyal Bilgiler öğretmeni oluşturmaktadır. Araştırma verileri Kabakçı-Yurdakul, ve arkadaşları (2012) tarafından geliştirilen Teknopedagojik Eğitim Yeterlikleri Ölçeği ve Görüşme Formu aracılığı ile toplanmıştır. Çalışm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…While Özer and Albayrak Özer (2017) stated that preservice teachers think that the use of web 2.0 applications will save time and facilitate the education process, Efe (2014), Fırat, andKöksal (2017) have concluded that pre-service teachers' tendencies towards the use of web 2.0 tools in education are weak. In order to ensure that teachers can effectively use the new elements of developing technology in their lessons (Kaya & Yazıcı, 2019), they need to gain extensive experience in the use of technology in social studies teaching in the lessons they have taken during their education (Shin et al, 2019). In the study conducted by Vannatta and Nancy (2014), it was determined that teachers who improve themselves in the use of technology in their daily life and who are willing to learn how to use technology are more likely to use technology in the classroom.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…While Özer and Albayrak Özer (2017) stated that preservice teachers think that the use of web 2.0 applications will save time and facilitate the education process, Efe (2014), Fırat, andKöksal (2017) have concluded that pre-service teachers' tendencies towards the use of web 2.0 tools in education are weak. In order to ensure that teachers can effectively use the new elements of developing technology in their lessons (Kaya & Yazıcı, 2019), they need to gain extensive experience in the use of technology in social studies teaching in the lessons they have taken during their education (Shin et al, 2019). In the study conducted by Vannatta and Nancy (2014), it was determined that teachers who improve themselves in the use of technology in their daily life and who are willing to learn how to use technology are more likely to use technology in the classroom.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%